Vitamin C Status in Hospitalized Adults According to Subjective Global Assessment Method. Issue 6 (22nd October 2018) - Avelino, Dewelyn Dias; Maltos, André Luiz; Portari, Guilherme Vannucchi; Gonçalves, Álisson de Carvalho; da Cunha, Daniel Ferreira
Abstract: Background: The subjective global assessment (SGA) is a powerful tool for nutrition status assessment. Our aim was to compare vitamin C serum levels among patients classified as A, B, or C in the SGA. Methods: One hundred‐and‐fifty adults in the wards of the University Hospital participated in this study. Besides SGA, all cases were submitted to anthropometry, bioelectrical impedance analysis (BIA), and 24‐hour dietary recall. Laboratory data included blood hemoglobin, serum ferritin, serum albumin, transferrin, C‐reactive protein (CRP), and vitamin C. Acute phase response was defined by serum CRP > 0.5 mg/dL; low serum vitamin C was defined by serum levels < 0.4 mg/dL. Analysis of variance and χ 2 tests were used to compare groups; P < 0.05 was considered significant. Results: Patients were diagnosed as SGA A (n = 76), B (n = 38), or C (n = 36) and showed different anthropometry and BIA. The same occurred, respectively, with vitamin C (median; range, in mg/day) intake (55.0; 4.7–140.6 vs 34.0; 10.3–244.2 vs 15.8; 2.3–124.0) and high (%) CRP (88.3 vs 65.8 vs 48.7) and low (%) vitamin C serum levels (21.1 vs 34.2 vs 63.9). Conclusion: Patients with worst nutrition parameters (SGA C) showed lower ascorbic acid serum levels than those classified as SGA A or B. These results are in accordance with reduced vitamin C intake and the presence of acute phase response.